LEGISLASI HAK TANGGUNGAN BAGI LEMBAGA PEMBIAYAAN - Girang Jayano (Muhammadiyah Law Review Journal, 2019)
To overcome the narcotics problem, the Indonesian government continues to strive to eradicate narcotics crimes by forming a Provincial National Narcotics Agency, formed based on Presidential Decree No. 23/2009 concerning the National Narcotics Agency. This research is motivated by the problem of abuse and illicit trafficking of narcotics that never ends even increasing every year. The problem in this study is how is the role of the National Narcotics Agency in Lampung Province in preventing narcotics abuse and whether the factors causing the increase in the number of narcotics abuse in Lampung Province. The method used in this research is empirical juridical. Data collection techniques used in this study were interviews, direct observation of spaciousness and approach with several sources in order to get a clear picture of the main problems that actually occur. Based on the results of research conducted by the National Narcotics Agency of Lampung Province in doing prevention and abuse of narcotics in Lampung Province is good but not optimal. Lampung Province National Narcotics Agency does drugs handling through counseling and rehabilitation of drug users, but public awareness is a great hope for the Lampung Province National Narcotics Agency or law enforcers not to use drugs for the better Indonesian people.